Challenges of Women working as Engineers: A comparative study between Kosovo and Ireland. Issue 13 (2021) - Bula, Ines; Kent, Mary Doyle; Bula, Edin; Hajrizi, Edmond
Abstract: The primary focus of this paper is to investigate the challenges of women working as engineers in Kosovo. A comparison is made with Ireland. It focuses on the lack of support from the employer, society itself and family. This research is divided in two continuous papers. In this first paper educational data, employment data and personal data from Kosovo and Ireland will be presented which has been gathered February 2021. The qualitative approach used in this research will focus on interviews with women working in Kosovo and Ireland and will ask questions about their perceived educational, employment, personal, socio-economic difficulties. One focus of this work will be, in hindsight, if women had the choice again, would they choose the engineering profession? Through this detailed analysis a clear picture will emerge of the challenges of Kosovar and Irish women during education and employment in the field of engineering. Also, as there is such a small number of women in the field of engineering, we ask the question is there a significant amount of human potential being unused, misused or underuse? How does the division of professions, based on traditional gender roles, lose out on human, institutional and global values?